2015
DOI: 10.1007/s00018-015-2078-9
|View full text |Cite
|
Sign up to set email alerts
|

Linking DNA polymerase theta structure and function in health and disease

Abstract: DNA Polymerase theta (Pol θ) is an error-prone A-family polymerase that is highly conserved among multicellular eukaryotes and plays multiple roles in DNA repair and the regulation of genome integrity. Studies conducted in several model organisms have shown that Pol θ can be utilized during DNA interstrand crosslink repair and during alternative end-joining repair of double-strand breaks. Recent genetic and biochemical studies have begun to elucidate the unique structural features of Pol θ that promote alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 89 publications
(145 reference statements)
0
48
0
Order By: Relevance
“…Human Pol θ was shown to interact with Orc2 and Orc4 and thus can localize to replication origins (12). It additionally was suggested that Pol θ is important for the temporal regulation of origin firing, although its exact role remains unclear (12). In contrast, our results show that the timing of origin firing is maintained in lig4; mus308, albeit reduced, and mus308 alone has no effect on the level of origin firing during amplification.…”
Section: How Might Various Repair Mechanisms Affect Replication Forkmentioning
confidence: 45%
See 4 more Smart Citations
“…Human Pol θ was shown to interact with Orc2 and Orc4 and thus can localize to replication origins (12). It additionally was suggested that Pol θ is important for the temporal regulation of origin firing, although its exact role remains unclear (12). In contrast, our results show that the timing of origin firing is maintained in lig4; mus308, albeit reduced, and mus308 alone has no effect on the level of origin firing during amplification.…”
Section: How Might Various Repair Mechanisms Affect Replication Forkmentioning
confidence: 45%
“…This overexpression may confer an advantage to cancer cells and alleviate replication stress by promoting DSB repair at sites of replication fork collapse. We therefore investigated whether Pol θ, encoded by mutagen-sensitive 308 (mus308) in Drosophila (12), is involved in DSB repair during rereplication in Drosophila follicle cells and whether its loss might impair the production of proteins involved in eggshell development. Indeed, we found that null mutants in mus308 exhibit a sporadic eggshell defect ( Fig.…”
Section: Absence Of Pol θ Perturbs Chorion Gene Transcription and Eggmentioning
confidence: 99%
See 3 more Smart Citations